Perspectivas de desenvolvimento de células a combustível sob a ótica da triz - Waack Bambace, Luís Antonio; Nishimori, Miriam; Castro, Alfredo (Revista Ciências Exatas, 2009)
This paper discuss the perspectives of fuel cell development by the TRIZ point of view. Itconsiders the performance of existing systems for conversion of chemical energy in electricity ormechanical energy and performance perspectives of eight different fuel cell types, given byanalytical models, as well as the evolution rates, and patent filing rates of the types with massiveresearch to evaluate the future scenarios of fuel cells usage in different market application niches.In fact the TRIZ and the Theory of Constraints, TOC, have in common the fact that both looks for theelimination to the main cause of the system performance limitations. By the TRIZ point of view, atechnical contradiction is always the limiting issue, and as it is eliminated there is a significantperformance improvement, but in general people use trade offs instead of looking for innovation.Fuel cells of different types have lots of technical contradictions, linked, for instance, to transportphenomena, processes, efficient use of catalyst among others. Selecting inventive principles tosolve these contradictions, and detail their use in a second step is more effective than a randomtrial and error search for a better system.